Reduced PPARγ2 expression in adipose tissue of male rat offspring from obese dams is associated with epigenetic modifications. Issue 5 (8th January 2018) - Lecoutre, Simon; Pourpe, Charlène; Butruille, Laura; Marousez, Lucie; Laborie, Christine; Guinez, Ce´line; Lesage, Jean; Vieau, Didier; Eeckhoute, Je´rome; Gabory, Anne; Oger, Fre´de´rik; Eberle´, Delphine; et al.
Abstract : According to the Developmental Origin of Health and Disease (DOHaD) concept, maternal obesity and accelerated growth in neonates program obesity later in life. White adipose tissue (WAT) has been the focus of developmental programming events, although underlying mechanisms remain elusive. In rodents, WAT development primarily occurs during lactation. We previously reported that adult rat offspring from dams fed a high‐fat (HF) diet exhibited fat accumulation and decreased peroxisome proliferator‐activated receptor γ (PPARγ) mRNA levels in WAT. We hypothesized that PPARγ down‐regulation occurs via epigenetic malprogramming which takes place during adipogenesis. We therefore examined epigenetic modifications in the PPARγ1 and PPARγ2 promoters in perirenal (pWAT) and inguinal fat pads of HF offspring at weaning (postnatal d 21) and in adulthood. Postnatal d 21 is a period characterized by active epigenomic remodeling in the PPARγ2 promoter (DNA hypermethylation and depletion in active histone modification H3ac and H3K4me3) in pWAT, consistent with increased DNA methyltransf erase and DNA methylation activities. Adult HF offspring exhibited sustained hypermethylation and histone modification H3ac of the PPARγ2 promoter in both deposits, correlated with persistent decreased PPARγ2 mRNA levels. Consistent with the DOHaD hypothesis, retained epigenetic marks provide a mechanistic basis for the cellular memory linking maternal obesity to a predisposition for later adiposity.—Lecoutre, S., Pourpe, C., Butruille, L., Marousez, L., Laborie, C., Guinez, C., Lesage, J., Vieau, D., Eeckhoute, J., Gabory, A., Oger, F., Eberle´, D., Breton, C. Reduced PPARγ2 expression in adipose tissue of male rat offspring from obese dams is associated with epigenetic modifications. FASEB J. 32, 2768–2778 (2018). www.fasebj.org